2022
DOI: 10.3389/fpsyg.2022.890418
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hospitality Work Environment on Employees’ Turnover Intentions During COVID-19 Pandemic: The Mediating Role of Work-Family Conflict

Abstract: Employees’ turnover intentions and work-family conflict as a result of the hospitality work environment are considered the major global challenges confronted by hospitality organizations, especially in the era of COVID-19. This study aims at identifying the impact of the hospitality work environment on work-family conflict (WFC), as well as turnover intentions and examining the potential mediating role of WFC in the relationship between work environment and turnover intentions, during the COVID-19 pandemic in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 102 publications
(114 reference statements)
3
31
0
1
Order By: Relevance
“…The turnover intentions were appraised by means of an improved three-item measure scale in line with Abdou et al [ 55 ]. These items are as follows: (1) If you are given a choice to choose once again, you will decide to work in another occupation/job; (2) At present, you are surely considering saying goodbye to your current job in the hotel; (3) Perhaps I will make an effort to find a new occupation/job within next year or less.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The turnover intentions were appraised by means of an improved three-item measure scale in line with Abdou et al [ 55 ]. These items are as follows: (1) If you are given a choice to choose once again, you will decide to work in another occupation/job; (2) At present, you are surely considering saying goodbye to your current job in the hotel; (3) Perhaps I will make an effort to find a new occupation/job within next year or less.…”
Section: Methodsmentioning
confidence: 99%
“…Labor turnover was seen as a two-dimensional concept, divided into voluntary and involuntary turnover, between an individual leaving a job and joining another workplace [ 53 , 54 ]. The turnover intentions were weighed with the help of an adapted three-item measure scale on the basis of Abdu [ 55 ]. These three items are as follows: (1) At present, I am surely considering resigning from my current employment in the resort; (2) Perhaps I will make an effort to find a new occupation within a year; (3) If I have a choice of choosing again, I will opt for working in another profession [ 40 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies (Salleh et al, 2012;Kamarulzaman et al, 2015;Abdou et al, 2022)) have been done on the association between workload, pay, and job satisfaction. In the hotel sector, where sales of upscale services may be involved, salaries are sometimes supplemented by a range of incentive payment plans in addition to base pay.…”
Section: Workload and Pay Systemmentioning
confidence: 99%
“…Organizational commitment is also affected by fringe benefits for hotel managers, like birthday and social celebrations (Ahmad and Scott, 2015). Salary, however, can have a greater impact on turnover intention than on job satisfaction in the hotel industry, with co-worker relationships and the atmosphere having a far stronger effect (Wu, 2012;Salleh et al, 2012;Kamarulzaman et al, 2015;Abdou et al, 2022). According to Chan et al, (2015), workload contributed to employee attrition as a result of burnout among casino dealers.…”
Section: Workload and Pay Systemmentioning
confidence: 99%
“…Good governance must be followed. Previous studies show the effect of COVID-19 on the performance of the firms, RMG sectors, and other firms on a percentage basis and descriptive statistics only, such as Syed (2020), Khanam (2021), Kabir et al (2021), Ali et al (2021), Akpa et al (2022) and Abdou et al (2022) were the most recent work identified. Still, this study tries to capture the issues with perception index as well as with correlations analysis.…”
Section: Literature Reviewmentioning
confidence: 99%